Missing the biggest story – the UK regional press after Leveson. (1st March 2017) - Clark, Tor
Early in 2013 John Mair's swiftly produced edited collection of articles about the impact of the then-recent Leveson Report included two chapters on the regional press. My chapter offered statistical evidence to show that the regional press was the sector with the best track record in terms of complaints to the Press Complaints Commission (PCC). The chapter controversially predicted that any proposed regulation would have no impact on that sector. It hoped that Lord Justice Leveson's highlighting of the problems of the regional press and plea for recognition of its vital community role might prompt positive parliamentary activity. Four years later regulation has had no impact on the regionals, but the bigger issue of the basic viability of the sector remains unresolved. So how healthy is the UK regional press now? Is digital journalism a killer or a saviour? And how long can the regionals survive?